2016
DOI: 10.1021/acs.jpca.6b07932
|View full text |Cite
|
Sign up to set email alerts
|

Photoactivated Production of Secondary Organic Species from Isoprene in Aqueous Systems

Abstract: Photoactivated reactions of organic species in atmospheric aerosol particles are a potentially significant source of secondary organic aerosol material (SOA). Despite recent progress, the dominant chemical mechanisms and rates of these reactions remain largely unknown. In this work, we characterize the photophysical properties and photochemical reaction mechanisms of imidazole-2-carboxaldehyde (IC) in aqueous solution, alone and in the presence of isoprene. IC has been shown previously in laboratory studies to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
54
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(67 citation statements)
references
References 28 publications
12
54
1
Order By: Relevance
“…The oscillator strength for the S 0 S 1 excitation is zero, as it corresponds to a "symmetry forbidden" electronic transition, while that for the S 0 S 2 excitation is quite large and should correspond to the main transition involved in the broad, experimentally observed band in different solvents around 280 nm. 26,33,50 According to experimental measurements, the band exhibits a pronounced redshift from non-polar to polar solvents, and this was interpreted as an indication that the main transition in the band is  in origin, 26 as predicted by our calculations. Photophysical properties in pure water droplets.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…The oscillator strength for the S 0 S 1 excitation is zero, as it corresponds to a "symmetry forbidden" electronic transition, while that for the S 0 S 2 excitation is quite large and should correspond to the main transition involved in the broad, experimentally observed band in different solvents around 280 nm. 26,33,50 According to experimental measurements, the band exhibits a pronounced redshift from non-polar to polar solvents, and this was interpreted as an indication that the main transition in the band is  in origin, 26 as predicted by our calculations. Photophysical properties in pure water droplets.…”
Section: Resultssupporting
confidence: 76%
“…Imidazole derivatives such as IC are produced from glyoxal reactions in aqueous aerosol particles (see Refs 8,25 and references cited therein). IC has been the focus of many experimental studies 9,24,[26][27][28][29][30][31][32] but apart from some simple computations, 9 its photochemistry has not been investigated theoretically. Some measurements have revealed that IC can lead to significant SOA production, 29,30 although some others 31 suggest that more abundant photosensitizer species, such as humic-like substances, may contribute more significantly to SOA growth.…”
Section: Introductionmentioning
confidence: 99%
“…Phospholipids can be transported from seawater into sea spray aerosol (SSA) directly (Collins et al, 2016). They also can be further transformed into fatty acids through heterotrophic breakdown (Li-Beisson et al, 2019;Guschina and Harwood, 2006). Long-chain saturated fatty acids, such as palmitic acid and stearic acid, correspond to major constituents of the sea surface microlayer and are also detected in marine aerosols (Marty et al, 1979;Slowey et al, 1962;Wu et al, 2015;Hu et al, 2018;Kang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These photosensitized reactions have been shown in the laboratory to induce to an abiotic source of volatile organic compounds (VOCs) and secondary organic aerosols (SOA) in the marine boundary layer (Rossignol et al, 2016;Tinel et al, 2016;Bernard et al, 2016). Traces of photosensitizing species in the aerosol phase, such as imidazoles, quinones and nitrophenols also contribute to SOA formation through their promoting effect with just a few radical reactions (Li et al, 2016;Desyaterik et al, 2013;Pillar and Guzman, 2017).…”
Section: Introductionmentioning
confidence: 99%